2007
DOI: 10.1111/j.1745-7254.2007.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combination therapy with atenolol and amlodipine on blood pressure control and stroke prevention in stroke-prone spontaneously hypertensive rats

Abstract: Aim: To test the effects of atenolol and amlodipine, either alone or in combination, on blood pressure, blood pressure variability (BPV), baroreflex sensitivity (BRS), and the prevalence of stroke in stroke-prone spontaneously hypertensive rats (SHR-SP). Methods: In the first set of the study, 24 8-month-old, female SHR-SP rats were randomly divided into 3 groups. Blood pressure, heart period, and BRS were determined before and after the intragastric administration of atenolol (10 mg/kg) and amlodipine (1.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…11 Preliminary studies in stroke-prone spontaneously hypertensive rats have shown that significant synergism exists between atenolol and amlodipine in lowering and stabilizing blood pressure. 14 The results of our study confirmed that the combination therapy with atenolol/amlodipine is superior to atenolol monotherapy in patients with mild-to-moderate essential hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…11 Preliminary studies in stroke-prone spontaneously hypertensive rats have shown that significant synergism exists between atenolol and amlodipine in lowering and stabilizing blood pressure. 14 The results of our study confirmed that the combination therapy with atenolol/amlodipine is superior to atenolol monotherapy in patients with mild-to-moderate essential hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…The probability sum test was used to determine whether the effect of the combination of the two drugs was synergistic. This test was first proposed by Jin in 1980 31 and subsequently adapted for evaluating the synergism of two antihypertensive drugs 32,33 . In the present work, we found that in cultured neonatal rat cardiomyocytes, cell viability and cardiomyocyte apoptosis was markedly influenced by pretreatment with either losartan or simvastatin, and that these effects were markedly enhanced when the two drugs were used in combination.…”
Section: Discussionsupporting
confidence: 62%
“…This test was first proposed by Jin in 1980 [31] and subsequently adapted for evaluating the synergism of two antihypertensive drugs. [32,33] In the present work, we found that in cultured neonatal rat cardiomyocytes, cell viability and cardiomyocyte apoptosis was markedly influenced by pretreatment with either losartan or simvastatin, and that these effects were markedly enhanced when the two drugs were used in combination. The q values for cell viability and cardiomyocyte apoptosis were 1.31 and 1.21, respectively.…”
Section: Discussionmentioning
confidence: 48%